Development and Characterization of a Camelid Single Domain Antibody–Urease Conjugate That Targets Vascular Endothelial Growth Factor Receptor 2 - Tian, Baomin; Wong, Wah Yau; Uger, Marni D.; Wisniewski, Pawel; Chao, Heman (Frontiers in Immunology, 2017)
Angiogenesis is the process of new blood vessel formation and is essential for a tumor to grow beyond a certain size. Tumors secrete the pro-angiogenic factor vascular endothelial growth factor (VEGF), which acts upon local endothelial cells by binding to vascular endothelial growth factor receptors (VEGFR). In this study, we describe the development and characterization of V21-DOS47, an immunoconjugate that targets VEGFR2. V21-DOS47 is composed of a camelid single domain anti-VEGFR2 antibody (V21) and the enzyme urease. The conjugate specifically binds to VEGFR2 and urease converts endogenous urea into ammonia, which is toxic to tumor cells. Previously, we developed a similar antibody-urease conjugate, L-DOS47, which is currently in clinical trials for non-small cell lung cancer. Although V21 DOS47 was designed from parameters learned from the generation of L DOS47, additional optimization was required to produce V21 DOS47. In this study we describe the expression and purification of two versions of the V21 antibody: V21H1 and V21H4. Each was conjugated to urease using a different chemical cross-linker. The conjugates were characterized by a panel of analytical techniques including SDS-PAGE, SEC, Western blotting, and LC-MSE peptide mapping. Binding characteristics were determined by ELISA and flow cytometry assays. To improve the stability of the conjugates at physiologic pH, the pIs of the V21 antibodies were adjusted by adding several amino acid residues to the C-terminus. For V21H4, a terminal cysteine was also added for use in the conjugation chemistry. The modified V21 antibodies were expressed in the E. coli BL21 (DE3) pT7 system. V21H1 was conjugated to urease using the heterobifunctional cross-linker succinimidyl-[(N-maleimidopropionamido)-diethyleneglycol] ester (SM(PEG)2), which targets lysine resides in the antibody. V21H4 was conjugated to urease using the homobifunctional cross-linker, 1,8-bis(maleimido)diethylene glycol (BM(PEG)2), which targets the cysteine added to the antibody C-terminus. V21H4-DOS47 was determined to be the superior conjugate as the antibody is easily produced and purified at high levels, and the conjugate can be efficiently generated and purified using methods easily transferrable for cGMP production. In addition, V21H4-DOS47 retains higher binding activity than V21H1-DOS47, as the native lysine residues are unmodified.